Prioritising earthquake retrofitting in Wellington, New Zealand. Issue 4 (13th August 2021) - Hoang, Thoa; Noy, Ilan; Filippova, Olga; Elwood, Ken
Abstract : This study describes the application of multi‐criteria decision analysis (MCDA) to prioritise the seismic risk mitigation of existing buildings in earthquake‐prone Wellington, New Zealand. Through retrofitting or demolition, this is an important requirement in many cities around the Pacific Rim and in other high‐level seismic hazard locations. The prioritisation strategy proposed here, based on MCDA methods, can provide decision‐makers with a fast and reliable support tool for identifying the optimal sequencing of their retrofitting programmes. The premise of the MCDA analysis presented in this paper is that there are multiple criteria that determine societal prioritisation preferences; these are limited not just to life safety (often the explicit/exclusive priority of governments) and commercial value (the main concern of many building owners). The study demonstrates how different measures, within four general criteria—life safety and geo‐spatial, economic, and socio‐cultural roles—can be operationalised as a viable framework for establishing intervention policy priorities.